The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1462-2920.2006.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of Escherichia coli in continuous culture during adaptation to artificial sunlight

Abstract: Escherichia coli growing in continuous culture under continuous UVA irradiation exhibits growth inhibition with a subsequent adaptation to the stress. Transcriptome analysis was performed during transient growth inhibition and in the UVA light-adapted growth state. The results indicate that UVA light induces stringent response and an additional response that includes the upregulation of the synthesis of valine, isoleucine, leucine, phenylalanine, histidine and glutamate. The induction of several SOS response-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
0
29
1
Order By: Relevance
“…Additionally, the ranges of relative expression ratios determined here (minimum, R ϭ 0.5; maximum, R ϭ 4.4) are similar to expression levels in previous studies of E. faecalis in oligotrophic seawater systems (6, 7), which found maximum changes in expression of ϳ3-fold by microarray. In contrast, some previous studies have observed larger expression changes in E. coli after sunlight exposure, but we expect this may be due to either the use of growth medium during sunlight exposure (9) or the use of a different method (i.e., transcriptome sequencing [RNA-seq]) to detect gene expression changes (26). Despite the fact that large changes in expression were not detected here, the approximately stable expression levels across samples in both systems suggest that cells remain transcriptionally active, even after the majority of cells are not culturable.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Additionally, the ranges of relative expression ratios determined here (minimum, R ϭ 0.5; maximum, R ϭ 4.4) are similar to expression levels in previous studies of E. faecalis in oligotrophic seawater systems (6, 7), which found maximum changes in expression of ϳ3-fold by microarray. In contrast, some previous studies have observed larger expression changes in E. coli after sunlight exposure, but we expect this may be due to either the use of growth medium during sunlight exposure (9) or the use of a different method (i.e., transcriptome sequencing [RNA-seq]) to detect gene expression changes (26). Despite the fact that large changes in expression were not detected here, the approximately stable expression levels across samples in both systems suggest that cells remain transcriptionally active, even after the majority of cells are not culturable.…”
Section: Discussioncontrasting
confidence: 46%
“…A number of studies have therefore investigated bacterial photoinactivation in the context of environmental water quality (1)(2)(3)(4)(5)(6)(7), with further studies also focusing on photoinactivation in drinking water treatment (8)(9)(10)(11), photodynamic therapy (12)(13)(14)(15), and wastewater treatment (16)(17)(18)(19)(20). Bacteria can be inactivated by sunlight by direct and indirect mechanisms.…”
mentioning
confidence: 99%
“…Researchers have found that growth rates and conditions are important determinants of how E. coli bacteria respond to stress (4,5,29). The E. faecalis bacteria used to seed the experiments presented here were grown to late stationary phase and then stored in filtered seawater at 4°C for 12 h before the start of the experiment.…”
Section: Fig 1 E Faecalis Inactivation Was Measured With Mei Idexx mentioning
confidence: 99%
“…The SOS regulon of Escherichia coli comprises 31 experimentally proven damage-inducible (din) genes (Fernández de Henestrosa et al, 2000). Microarray analyses identified upregulation of 163 genes when E. coli cells were exposed to UV light (Berney et al, 2006). The SOS regulon of the Gram-positive model organism Bacillus subtilis consists of 63 (hitherto known) genes organized in 23 operons (Friedberg et al, 1995;Goranov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%